Pemanfaatan Teknologi ICT Dalam Bidang Pendidikan Vokasional Di Indonesia - Irwanto, Irwanto (9 772338317006, 2024)
Abstract: Vocational education plays an important role in preparing students to enter the workplace with relevant expertise. In today's digital age, the use of information and communication technology (ICT) has become a must to improve learning efficiency in vocational education institutions. This article aims to explore how the use of technology can improve the learning experience of students in vocational schools. Literature studies are a series of research activities involving the collection, reading, recording, and processing of information from relevant written sources. As an example of a case study, we will review how vocational schools have successfully improved learning by using an online learning platform. With this platform, students can access learning materials, tasks, and exams online, as well as interact with teachers and fellow students through available discussion and collaboration features. The evaluation results showed significant improvements in student participation, material understanding, and overall academic results. The use of technology has brought a major change in the learning process in vocational schools. With careful planning and robust support, technology can be an effective tool in enhancing students’ learning experiences, preparing them to face the challenges of an increasingly complex world of work, and enhancing their competitiveness in a dynamic global job market. Keywords: Vocational education, Information and Communication Technology, Online Learning PlatformDOI: 10.23960/jmmp.v12.i2.2024.32158